(untitled) (CIPEEX, 2025)
Introduction: Anxiety is among the most common mental disorders, but it is often overlooked and inadequately treated, a factor contributing to its chronic nature. Pharmacists play a key role in screening, guiding treatment, and ensuring patient adherence to treatment, whether pharmacological or non-pharmacological. Objective: To conduct a comprehensive review of the existing literature on the role of pharmacists in the treatment of anxiety symptoms. Methodology: This literature review uses the PICO framework. The inclusion criteria for this study were as follows: the studies in question must have been published in the last decade, in English, and must have been cross-sectional studies or controlled clinical trials. A search was conducted in August 2025 in the BVS and SciELO databases. The descriptors used in the search were combined with Boolean operators as follows: pharmaceutical care OR pharmacist AND anxiety disorders. Results: The results indicate that pharmacists play an effective role in promoting medication adherence, enabling closer multidisciplinary monitoring and, in community pharmacies, promoting the rational use of psychotropic medications and preventing the progression of anxiety symptoms. Conclusion: The review highlights the crucial role of pharmacists in managing anxiety, promoting treatment adherence, rational medication use, and facilitating access to mental health care. Their integration into multidisciplinary teams and community pharmacies has been shown to contribute to reducing anxiety symptoms and improving patients’ quality of life.